Social factors influencing on the popularization of aesthetic group gymnastics in Russia - Zakharova Y.V.; Balaeva O.E. (Theory and Practice of Physical Culture, 2024)
The purpose of the study is to identify the main social factors that should stimulate interest in group classes in aesthetic gymnastics in Russia, which, therefore, should lead to the popularization of this sport. Methodology and organization of the study. To assess the situation with the modern development of aesthetic group gymnastics in our country, 7 experts were involved: representatives of physical education – 2 experts, coaches-teachers – 5 experts. We found out how many years the specialists have worked in their positions - this is extremely important in our survey, since one of the control signs is the work experience in the field of physical culture and sports for managers - at least three years; for the coaching staff - at least 10 years. 7 out of 7 experts have higher education in the field of physical culture and sports. To solve this problem, a questionnaire was developed in which experts expressed the following opinion. To the question: "What do you think influences girls more when choosing a sport?" half of the experts (50%) noted that the choice of a sport is influenced by the advice of friends, teachers, and supervisors. 35% believe that the final choice is influenced by imitation of athletes and the desire to be like them. And only 15% of experts refer to the popularity of the sport itself. Evaluating the results of the survey to the question: "What do you think girls strive for when doing sports?", 68% of experts replied that they "maintain good physical shape, improve the body." 16% of experts believe that one of the main goals of sports is to achieve high results in competitions. The remaining 16% are of the opinion that the goal of gymnasts is to spend their free time in an interesting way. To the next question: "Is motivation one of the important reasons for playing sports?" the experts unanimously answered "yes" (100%). After answering this question, the experts were asked to select the most important factors affecting motivation to exercise, as well as to note the less important ones. Representatives of physical education, coaches-teachers of rhythmic gymnastics and coaches-teachers of aesthetic group gymnastics noted the most important factors: praise, encouragement of the coach and rivalry, and rivalry, according to coaches-teachers of rhythmic gymnastics, far exceeds all other factors (35%), which is explained by the specifics of this sport. The same cannot be said about the representatives of aesthetic group gymnastics, where team spirit, coach’s instructions and, again, encouragement play an important role. The opinions of all experts agreed on the choice of a factor related to material indicators (money and awards): all 7 experts noted that money is an unimportant factor for motivation to play sports. Conclusions. Thus, in the course of our survey, experts identified a certain set of important objective social factors, which, in their opinion, influence the popularization and promotion of aesthetic group gymnastics. However, experts believe that this process is more influenced by the formation of personal interest and motivation for practicing this sport among modern girls.